Voice of Resistance: Feminist Stylistic Analysis in the Film Wolfwalkers 2020 - Fitriyani, Murni Nur; Ningsih, Wahyu; Rangkuti, Rahmadsyah (Journal of English Language and Education, 2025)
This study explores how female agency and resistance are represented in the animated film Wolfwalkers (2020) through the lens of Feminist Stylistics, as proposed by Sara Mills. The analysis focuses on linguistic features such as naming, transitivity, and sentence structure to uncover how the film challenges traditional gender roles and conveys themes of empowerment. The findings reveal that Wolfwalkers portrays its female characters as independent, courageous, and capable of subverting patriarchal authority. Through stylistic choices in both dialogue and narration, the film articulates a feminist discourse that foregrounds solidarity and transformation. This research contributes to feminist stylistic studies by demonstrating how language functions as a tool for resistance and gender redefinition in animated storytelling.